2013
DOI: 10.1007/s00253-013-5074-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized glutathione fermentation using Saccharomyces cerevisiae engineered for glutathione metabolism

Abstract: Glutathione is a valuable tripeptide that is widely used in the pharmaceutical, food, and cosmetic industries. Intracellular glutathione exists in two forms, reduced glutathione (GSH) and oxidized glutathione (GSSG). Most of the glutathione produced by fermentation using yeast is in the GSH form because intracellular GSH concentration is higher than GSSG concentration. However, the stability of GSSG is higher than GSH, which makes GSSG more advantageous for industrial production and storage after extraction. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Previously, we reported that an S. cerevisiae strain over-expressing GSH1/GSH2 constructed by a cocktail δ-integration method (Yamada et al 2010) showed higher total glutathione content compared with the parental strain (Hara et al 2012). Recently, we also showed that the deletion of the GLR1 gene was critical to enhancing the GSSG content (Kiriyama et al 2013). Therefore, in this study, we used the GCIΔGLR1 strain as platform strain for further improvement of GSSG production.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Previously, we reported that an S. cerevisiae strain over-expressing GSH1/GSH2 constructed by a cocktail δ-integration method (Yamada et al 2010) showed higher total glutathione content compared with the parental strain (Hara et al 2012). Recently, we also showed that the deletion of the GLR1 gene was critical to enhancing the GSSG content (Kiriyama et al 2013). Therefore, in this study, we used the GCIΔGLR1 strain as platform strain for further improvement of GSSG production.…”
Section: Discussionmentioning
confidence: 90%
“…In S. cerevisiae, Glr1 has been identified as a glutathione reductase (Grant and Dawes 1996). Recently, we constructed a GCIΔGLR1 strain by deleting the GLR1 gene from the genome of the GCI strain, which increased the GSSG/GSH ratio by about 2.2-fold compared with the GCI strain (Kiriyama et al 2013). Therefore, the combined effect of over-expression of the thiol oxidase and deletion of glutathione reductase would be expected to synergistically increase the GSSG content of S. cerevisiae.…”
Section: Over-expression Of Thiol Oxidase In a Strain Lacking Glutathmentioning
confidence: 97%
See 2 more Smart Citations
“…36 It was reasonable to hypothesize that the ATP effects may be due to its influence on the synthesis of GSH with its important role in our system. 26,27 Interestingly, when the GSH contents were determined in the Δatp1 strain, the tendency of GSH levels increasing with fluorescence intensities, referred to above, did not appear ( Figure 3A).…”
Section: Discussionmentioning
confidence: 99%